A systematic review exploring the content and outcomes of interventions to improve psychological safety, speaking up and voice behaviour - Róisín O'Donovan; Eilish McAuliffe (BMC, 2020)
Abstract Background Having psychologically safe teams can improve learning, creativity and performance within organisations. Within a healthcare context, psychological safety supports patient safety by enabling engagement in quality improvement and encouraging staff to speak up about errors. Despite the low levels of psychological safety in healthcare teams and the important role it plays in supporting patient safety, there is a dearth of research on interventions that can be used to improve psychological safety or its related constructs. This review synthesises the content, theoretical underpinnings and outcomes of interventions which have targeted psychological safety, speaking up, and voice behaviour within a healthcare setting. It aims to identify successful interventions and inform the development of more effective interventions. Methods A key word search strategy was developed and used to search electronic databases (PsycINFO, ABI/Inform, Academic search complete and PubMed) and grey literature databases (OpenGrey, OCLC WorldCat, Espace). Covidence, an online specialised systematic review website, was used to screen records. Data extraction, quality appraisal and narrative synthesis were conducted on identified papers. Results Fourteen interventions were reviewed. These interventions fell into five categories. Educational interventions used simulation, video presentations, case studies and workshops while interventions which did not include an educational component used holistic facilitation, forum play and action research meetings. Mixed results were found for the efficacy or effectiveness of these interventions. While some interventions showed improvement in outcomes related to psychological safety, speaking up and voice, this was not consistently demonstrated across interventions. Included interventions' ability to demonstrate improvements in these outcomes were limited by a lack of objective outcome measures and the ability of educational interventions alone to change deeply rooted speaking up behaviours. Conclusion To improve our understanding of the efficacy or effectiveness of interventions targeting psychological safety, speaking up and voice behaviour, longitudinal and multifaceted interventions are needed. In order to understand whether these interventions are successful, more objective measures should be developed. It is recommended that future research involves end users in the design phase of interventions, target both group and organisational levels, ensure visible leader support and work across and within interdisciplinary teams. Prospero registration number CRD42018100659.